Influence of the weather conditions of the growing season on the biometric indices and yield of switchgrass - Кулик, М. І.; Рожко, І. І. (Scientific Progress & Innovations, 2017)
The influence of weather conditions of vegetation on the variability of the elements of productivity (height and density of stems) of switchgrass is determined. The influence of average daily temperature of air and the amount of precipitation during vegetation of plants on the yield of phytomass of culture in terms of research years is determined. The correlation between quantitative indices of plants (elements of productivity) of the third–sixth years of vegetation and yield of phytomass of switchgrass is shown. It has been established that the yield of dry vegetative mass of switchgrass is largely determined by the number of stems per unit area in close correlation with the average daily temperature of air, to a less extent – the height of plants and the amount of precipitation during the vegetation period.